Стан, перспективи та досвід формування конфліктологічної культури майбутніх працівників патрульної та кіберполіції - Гіренко, С. П.; Girenko, S. P.; Ларіонов, С. О.; Larionov, S. O.; Сергій Гіренко (Право і безпека. – 2016. – № 4 (63). – С. 121–127, 2016)
Розглянуто деякі психолого-педагогічні аспекти конфліктологічної підготовки майбутніх працівників поліції. Визначено змістові компоненти навчальних дисциплін конфліктологічного спрямування в контексті формування їх професійної культури.

The authors of the article have studied some psychological and pedagogical aspects of conflict training of future police officers. It has been stated that the practice of psychological support of professional work in the National Police of Ukraine rarely uses the advanced psychotherapeutic experience, while dealing with conflict situations. Accordingly, there is no practice and reference to the departmental psychologists for the assistance in resolving conflicts and acute conflict states of police personnel. The authors have provided the results of the survey of police officers, according to which the most common causes of conflict among police officers are not taking personal and business qualities of leaders, lack of professionalism of colleagues, “barriers” of other departments of the Ministry of Internal Affairs, etc. The content components of academic disciplines of conflict direction in the context of the formation of their professional culture have been determined. It has been demonstrated that the absence of specific academic disciplines does not create the pedagogical conditions for the formation of conflict competence of an officer of “new” police during his training. A competent approach to raise conflict competence and conflict culture that ensures the readiness of police officers to conflict management. The authors have suggested the system of elements of conflict culture, which reflects the social, professional, individual and psychological conditions for effective law enforcement activities in the context of psychological (rejection of the reforms and new police structure) and physical (attempts to harm a police officer, trying to avoid coercion, etc.) resistance from citizens.

Рассмотрены некоторые психолого-педагогические аспекты конфликтологической подготовки будущих работников полиции. Определены содержательные компоненты учебных дисциплин конфликтологического направления в контексте формирования их профессиональной культуры.
Состояние, перспективы и опыт формирования конфликтологической культуры будущих сотрудников патрульной и киберполиции
The state, perspectives and experience in forming conflict culture of future officers of patrol and cyberpolice
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Юридична психологія. Legal psychology. Юридическая психология; комунікація; конфлікт; конфліктологічна культура; Національна поліція України. National police of Ukraine. Национальная полиция Украины; тренінг; стрес; патрульна поліція; кіберполіція; коммуникация; конфликт; конфликтологическая культура; Национальная полиция Украины; тренинг; стресс; патрульная полиция; киберполиция; communication; conflict; conflict culture; National police of Ukraine; training; stress; patrol police; cyberpolice; поліція; полиция; police